Paradas e fugas súbitas dos fluxos de capital nos países emergentes: Fatores globais e locais - Marcos Antonio C. da Silveira; Ajax Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The financial account of the balance of payments aggregates a set of heterogeneous flows, with marked differences in terms of purpose, risk, maturity and liquidity. With this perspective, the paper analyzes the factors that explain comparatively extreme events occurred in the flows of the three main headings of the financial account: direct investment, portfolio investment and account for loans and financing. These events are identified in the literature as sudden stops in net capital inflows from residents or the sudden flight of capital from residents. The paper concludes that the global risk is the only relevant variable to explain the events of sudden stop in net inflow of foreign capital of almost all forms of capital. The explanatory power of each local variable differs between the types of capital flow.
Keywords: F21; F32; 330; sudden stop; sudden flight; financial account; flow of external capital